Factors affecting legal compliance in construction procurement of local administrative organizations - Kongsong, Waranon; Jampakhao, Wasan; Snongtaweeporn, Teeradej; Roikulcharoen, Sumet; Chaiwat; Thammapornram, Chaleeporn (Edelweiss Applied Science and Technology, 2025)
This article aims to study the factors affecting legal compliance in the construction procurement of local administrative organizations. A quantitative research methodology was employed using a rating scale questionnaire distributed to experts from local administrative organizations. The research findings revealed that the overall factors influencing legal compliance in construction contracts had an average score of 3.53 with a standard deviation of 0.86, which is considered a high level. When analyzed by category, personnel factors had the highest average score of 3.65 (high level), followed by factors related to compliance with other laws (average = 3.63, high level). Coordination factors and support factors had average scores of 3.46 and 3.40, respectively, which are considered moderate. The study indicated that personnel factors had the greatest impact on legal compliance. Therefore, local administrative organizations should enhance the competency of their personnel in relevant areas of law concerning public construction procurement, construction standards, and other applicable regulations such as the Engineers Act, the Town Planning Act, and the Building Control Act. This is to ensure that the procurement process is conducted efficiently and strictly according to legal requirements.